Pengaruh Fasilitas Penunjang Kawasan Wisata terhadap Kepuasan Pengunjung (Studi Kasus Wisata Pantai Ampenan) - Andini, Saudari Warti; Salahuddin, Muh.; Wijaya, Pongky Arie (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to determine the effect of tourism support facilities on visitor satisfaction. The population in this study were visitors to the Ampenan Beach Tourism object. The sample used was 100 respondents. Sampling using nonprobability sampling technique, namely incidental sampling technique. Data analysis using simple linear regression analysis techniques, F test and t test. The results show that there is a significant influence between facilities on tourism and visitor satisfaction at Ampenan Beach is 54.7% while 45.3% is influenced by other factors with the determinant coefficient value (R Square) is 0.547 and a significance value of 0.000.